2013
DOI: 10.1080/10106049.2012.748830
|View full text |Cite
|
Sign up to set email alerts
|

Application of frequency ratio and likelihood ratio model for geo-spatial modelling of landslide hazard vulnerability assessment and zonation: a case study from the Sikkim Himalayas in India

Abstract: The Likelihood Ratio (LR) Model has been applied as an improvement upon the Frequency Ratio (FR) that computes the ratio of the percentage of the landslide pixels to the percentage of the non-landslide pixels instead of the total number of pixels used in the denominator as in case of the FR. The comparative assessment of the two techniques is made through spatial modelling of GIS vector data using the ArcGIS software. Two different Landslide Information Values were computed for each polygon element of the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…These rocks are highly vulnerable to landslide as the presence of well-developed foliation plains and joints. Our results are in agreement with Sharma et al (2014); Chawla et al (2018) which have found that landslide distribution are high on phyllite, lingtse granite gneiss and Darjeeling gneiss. Within lineament classes, high PLR is observed in high lineament subclass (Table 5).…”
Section: Rf-plr Modelsupporting
confidence: 93%
“…These rocks are highly vulnerable to landslide as the presence of well-developed foliation plains and joints. Our results are in agreement with Sharma et al (2014); Chawla et al (2018) which have found that landslide distribution are high on phyllite, lingtse granite gneiss and Darjeeling gneiss. Within lineament classes, high PLR is observed in high lineament subclass (Table 5).…”
Section: Rf-plr Modelsupporting
confidence: 93%
“…The analysis shows that most studies have used quantitative techniques, of which logistic regression has been most used [81][82][83]. Thereafter, frequency ratio and information value were used 16% and 9% of the studies, respectively [74,[84][85][86][87][88]. In terms of semi-quantitative models, AHP has been the most used method (Figure 8).…”
Section: Landslide Susceptibilitymentioning
confidence: 99%
“…In the same study area, the landslide vulnerability assessment and zonation was performed earlier using the same causative parameters and applying several methods. These include tri-variate approach (Sharma et al 2009a), landslide susceptibility assessment based on soil characteristics (Sharma et al 2009b(Sharma et al , 2012b, ranking of causative parameters (Sharma et al 2011), experts' weight and Shannon's entropy (Sharma et al 2012a), landslide density of the causative parameters (Sharma et al 2012c) and likelihood ratio approaches (Sharma et al (2012d), Fuzzy Logic (Sharma et al 2013).The present method of study introduces a new approach to perform the task of landslide susceptibility assessment. This approach integrates the concept of Shannon's entropy with the information value theory, to compute the landslide information values of the different polygons.…”
Section: Introductionmentioning
confidence: 96%